1998
DOI: 10.1091/mbc.9.8.2201
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Analysis of Interactions with Spc110p Reveals Distinct Functions of Spc97p and Spc98p, Components of the Yeast γ-Tubulin Complex

Abstract: The spindle pole body (SPB) in Saccharomyces cerevisiae functions as the microtubuleorganizing center. Spc110p is an essential structural component of the SPB and spans between the central and inner plaques of this multilamellar organelle. The amino terminus of Spc110p faces the inner plaque, the substructure from which spindle microtubules radiate. We have undertaken a synthetic lethal screen to identify mutations that enhance the phenotype of the temperature-sensitive spc110 -221 allele, which encodes mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 39 publications
5
74
0
Order By: Relevance
“…Indeed, biochemical and genetic studies have shown that the carboxyl terminus of Spc110p along with calmodulin is present at the central plaque (Sundberg et al, 1996) in a complex with Spc42p and a 35-kDa protein (Knopp and Schiebel, 1997). The amino terminus of Spc110p links the central plaque to the inner plaque through an interaction with Spc98p, a component of the yeast ␥-tubulin complex Sundberg and Davis, 1997;Nguyen et al, 1998). Because of the physical interactions of Spc110p with both the central and inner plaques, the absence of the inner plaque in the heparin-stripped cores could have led to a disruption of the organization of proteins in this region.…”
Section: Structural Organization Of the Spb In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, biochemical and genetic studies have shown that the carboxyl terminus of Spc110p along with calmodulin is present at the central plaque (Sundberg et al, 1996) in a complex with Spc42p and a 35-kDa protein (Knopp and Schiebel, 1997). The amino terminus of Spc110p links the central plaque to the inner plaque through an interaction with Spc98p, a component of the yeast ␥-tubulin complex Sundberg and Davis, 1997;Nguyen et al, 1998). Because of the physical interactions of Spc110p with both the central and inner plaques, the absence of the inner plaque in the heparin-stripped cores could have led to a disruption of the organization of proteins in this region.…”
Section: Structural Organization Of the Spb In Situmentioning
confidence: 99%
“…A high percentage of these proteins have predicted coiled-coil domains, including Spc42p, which forms a central crystalline core (Donaldson and Kilmartin, 1996;Bullitt et al, 1997), and Spc110p, which acts as a molecular spacer between the central and inner plaques (Kilmartin et al, 1993;Kilmartin and Goh, 1996). The amino terminus of Spc110p in turn interacts with Spc98p (Geissler et al, 1996;Sundberg and Davis, 1997;Nguyen et al, 1998), which along with Spc97p (Knopp and Schiebel, 1997) and Tub4p (Sobel and Snyder, 1995;Marschall et al, 1996;Spang et al, 1996) make up the ␥-tubulin complex at the MT ends at both the inner and outer plaques. Spc72p and Cnm67p localize to the outer plaque of the SPB (Wigge et al, 1998).…”
mentioning
confidence: 99%
“…In the budding yeast, a small ␥ tubulin complex composed of ␥ tubulin (Tub4p), Spc97p, and Spc98p (ϳ700 kDa) is bound to the nuclear side of the spindle pole body (the centrosome equivalent) through an interaction with Spc110p (Knop and Schiebel, 1997) and to the cytoplasmic side of the spindle pole body through Spc72p (Knop and Schiebel, 1998). Spc97p and Spc98p mediate binding of the complex to Spc110p and Spc72p (Knop and Schiebel, 1997;Knop and Schiebel, 1998;Nguyen et al, 1998). Although there is no apparent homology between their SPC97/98 interacting domains, chimeras formed by fusing the binding domain of one with the localization domain of the other can rescue knockouts of the proteins encoding the localization domains, suggesting that the two binding domains are functionally homologous (Knop and Schiebel, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This simpler regulatory network together with the extremely well-defined SPB offers many advantages for the studies of microtubule nucleation in budding yeast. A combination of genetic and two-hybrid analyses shows that the Tub4p complex is anchored to the inner plaque by interaction with Spc110p Nguyen et al, 1998). Spc110p is a major SPB protein that has a calmodulin binding domain at the C terminus embedded in the SPB core, and a Tub4p complex binding domain at the N terminus pointed toward the microtubule ends (Geiser et al, 1993;Kilmartin et al, 1993;Kilmartin and Goh, 1996;Spang et al, 1996b;Sundberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%